PENGEMBANGAN PRODUK “BERAS ANALOG” UNTUK MENINGKATKAN PENERIMAAN PASAR - Dian Novitasari, Aji Hermawan, dan Titi Candra Sunarti (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
The “analog rice” (artificial rice) is a new product that has difficulties to enter the Indonesian market. The aim of this research was to analyze the development of the analog rice to enter the market. The steps were divided into three stages, i.e. to analyze the attributes considered in purchasing rice grain, to analyze the level of satisfaction and dissatisfaction of the analog rice attributes, and to analyze the development priority of the analog rice attributes. The data were collected by interview and survey questionnaire. The data were processed using descriptive analysis, quantitative analysis, category frequency distribution, Kano method, and analysis of quality improvement index. This research resulted in that there were 17 attributes to be considered by respondents in purchasing rice grain. Fragrance was the analog rice attribute that had highest satisfaction effect, cleanliness was the analog rice attribute that had highest dissatisfaction effect, and the large size of grain was the analog rice attribute that had lowest satisfaction and also lowest dissatisfaction. The development priority of the analog rice attributes included good taste, economical price, fragrance, sticky texture, and product consistency after cooking.Keywords: artificial rice, food diversification, Kano method, product development